2017
DOI: 10.15448/1980-6523.2017.1.26441
|View full text |Cite
|
Sign up to set email alerts
|

Dental emergencies in public health services: what is the role of the Dental Surgeon?

Abstract: OBJECTIVE: To assess the opinions of Brazilian dental surgeons (DS) about their roles in Public Emergency Dental Services (PEDS). METHODS: A cross-sectional study was conducted with an intentional sample of 44 DS who worked at the PEDS in a large municipality in the central-western region of Brazil, in 2013. To collect data we designed, pretested and applied a self-administered questionnaire with Likert scale assertions about the DS duties, referral of patients and execution of dental procedures in PEDS. Post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…There is evidence of acknowledgment of the role of each of the points among network professionals (n=1)[29], but without any communication, protocols and reference flows (n=2)[28,30], with poor recognition of lines streams of care in the DEC (n=1). Studies conducted in the DEC reported diverging opinions among professionals about some activities to be performed, procedures and which to refer[30,31], while there is consensus on spontaneous demand access and on the use of the medical record, science dedicated to accommodation failures and the system of risk rating, referencing, continuing education and protocol with clinical and pharmacological guidelines, and failures in infrastructure resources. Also, professionals confirm the control of workload and additional workload for the night shift[30,31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence of acknowledgment of the role of each of the points among network professionals (n=1)[29], but without any communication, protocols and reference flows (n=2)[28,30], with poor recognition of lines streams of care in the DEC (n=1). Studies conducted in the DEC reported diverging opinions among professionals about some activities to be performed, procedures and which to refer[30,31], while there is consensus on spontaneous demand access and on the use of the medical record, science dedicated to accommodation failures and the system of risk rating, referencing, continuing education and protocol with clinical and pharmacological guidelines, and failures in infrastructure resources. Also, professionals confirm the control of workload and additional workload for the night shift[30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in the DEC reported diverging opinions among professionals about some activities to be performed, procedures and which to refer[30,31], while there is consensus on spontaneous demand access and on the use of the medical record, science dedicated to accommodation failures and the system of risk rating, referencing, continuing education and protocol with clinical and pharmacological guidelines, and failures in infrastructure resources. Also, professionals confirm the control of workload and additional workload for the night shift[30,31]. The profile of the emergency user outlined by the professional confirms the predisposing characteristics and needs obtained in this review, the majority affirms that the user does not have a referral document, but affirms that they guide their own search under the continuity of care[28].…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence of acknowledgment of the role of each of the points among network professionals (n = 1) [31], but without any communication, protocols and reference flows (n = 2) [30,32], and with poor recognition of the lines of streams of care in the DEC (n = 1). Studies conducted in the DEC reported diverging opinions among professionals about some activities to be performed, procedures and which to refer [32,33], while there was consensus on spontaneous demand access and on the use of the medical record, science dedicated to accommodation failures and the system of risk rating, referencing, continuing education and protocol with clinical and pharmacological guidelines, as well as failures in infrastructure resources. Additionally, professionals confirm the control of workload and additional workload for the night shift [32,33].…”
Section: Enabling Factors and Gapsmentioning
confidence: 99%
“…Studies conducted in the DEC reported diverging opinions among professionals about some activities to be performed, procedures and which to refer [32,33], while there was consensus on spontaneous demand access and on the use of the medical record, science dedicated to accommodation failures and the system of risk rating, referencing, continuing education and protocol with clinical and pharmacological guidelines, as well as failures in infrastructure resources. Additionally, professionals confirm the control of workload and additional workload for the night shift [32,33]. The profile of the emergency user outlined by the professional confirms the predisposing characteristics and needs obtained in this review.…”
Section: Enabling Factors and Gapsmentioning
confidence: 99%